ANALISIS PENCEMARAN UDARA TERHADAP MASYARAKAT SEKITAR PROTEK MASS RAPID TRANSIT (MRT) JAKARTA CP 103 (Studi Kasus: Jl. Fatmawati, Cipete Utara) - Nugroho, Akbar Amir; Rahmayanti, Henita; Murtinugraha, R. Eka (LPPM, Universitas Negeri Jakarta, 2020)
This study aims to determine the impact of what is most felt by the people around the MRT Jakarta CP 103 project, North Cipete, South Jakarta. This research uses sub-indicators of noise impact and air quality degradation to know the most significant effect and impact factor from air pollution felt by people around North Cipete and South Gandaria due to MRT Jakarta CP 103 construction project. The questionnaire was based on noise and air quality reduction theory, summarized in questionnaire question items to obtain primary data in the MRT Jakarta CP 103 Project community. This study shows that the impact of noise and decreasing air quality resulting from the MRT CP 103 project is likely to be felt by the surrounding community. The project organizers did not explain the impacts resulting from the project in the AMDAL document. These results obtained factors that trigger the effect of disease and material losses felt by the public, namely the use of heavy equipment on the project that produces air pollution. Keywords: air pollution, MRT, society